Technical, Economic, and Environmental Review of Waste to Energy Technologies from Municipal Solid Waste - Siti Jamilatun; Joko Pitoyo; Martomo Setyawan (Jurnal Ilmu Lingkungan, 2023)
Global municipal solid waste production and electricity demand gradually increased as a result of urbanization, population increase, and economic growth. The appropriate selection of Waste to energy (WTE) technologies needs consideration of energy efficiency, financial, and environmental aspects. This article discusses the technical, financial, and environmental side of existing WTE technologies. Waste-to-energy (WTE) technologies include thermal, physical, biochemical, and bio-electrochemical technology. Pyrolysis, gasification, and incineration are thermal technology used to generate energy from waste in the form of heat and syn-gas. Anaerobic digestion and landfill are biochemical technology to to generate energy from waste in the form of biogas. Physical technology is used to to generate energy from waste in the form of refuse-derived fuel (RDF). Microbial fuel cells (MFC) and microbial electrolysis cells (MEC) are the most recent WTE technology that produces electricity and hydrogen fuel. The results of the assessment of existing technology show that anaerobic digestion and landfill are low-cost WTE technology but have a low potential for energy generation. Plasma gasification is WTE technology with a high potential for energy generation, cold gas efficiency (CGE), carbon conversion efficiency (CCE), and H2/CO ratio, low CO2 emissions, and high operating costs. MEC has a high H2-potential for energy generation, low CO2 emissions, and the highest capital cost. Incineration is a common conversion technology with a low potential for energy generation, high CO2 emissions, and high capital costs. The selection of WTE technologies is influenced by technical, economic, and environmental factors.